To what extent does the personal data protection Act 2010 protect the personal data of the consumer: a legal analysis / Arianie Rush, Mariam Nasyitah Mahamad and Rozainasha Mohd Omar. - Mahamad, Mariam Nasyitah; Rush, Arianie; Mohd Omar, Rozainasha (2014)
There are a lot of complaints made by individuals that believed their personal data have been violated. There are several situations in which the individual might believe so for instance, one might receive unknown phone calls from strangers advertising random item. One might also encounter a situation in which their mobile phones keep receiving messages from unknown number advertising products. These messages sometimes contain the name and the address the owner of the phone correctly. The question is where did they get this kind of personal information and it is authorized by the law. If so, how would a person feel safe and protected to know that his or her personal data are floating in hands of strangers. Thus, this research seeks to determine on the extent of protection provided by the Personal Data Protection Act 2010 in matters relating to the personal data of consumer. This research also would further investigate on whether there is a need for amendment of the Personal Data Protection Act 2010 in order to safeguard consumers' personal data. In discussing on the need to amend the Act 2010, this research will also focus on comparison between other countries with similar law such as Singapore and Hong Kong. This research employs qualitative approach to empirical studies. This approach is presumed to be closer to the social sciences. Data collection in the qualitative approach is a combination of two methods namely interviews, and document analysis.